The effects of intradialytic resistance training on muscle strength, psychological well-being, clinical outcomes and circulatory micro-ribonucleic acid profiles in haemodialysis patients: Protocol for a quasi-experimental study - Zelko, Aurel; Skoumalova, Ivana; Kolarcik, Peter; Rosenberger, Jaroslav; Rabajdova, Miroslava; Marekova, Maria; Geckova, Andrea Madarasova; van Dijk, Jitse P; Reijneveld, Sijmen A; NEPHRO-team (Medicine, 2019)
BACKGROUND: Intradialytic resistance training (IRT) protects patients' muscle mass and functions against protein-energy wasting, malnutrition and cachexia. However, the evidence of the effects of such an intervention in haemodialysis patients is limited and not conclusive. To improve the applicability of such interventions, we need a better understanding of molecular, functional and psycho-social adaptation in dialysed patients following a physical training. Therefore, the aim of this study is to investigate the effects of IRT on lower extremity muscle functions, quality of life, and anxiety and depression, clinical outcomes and circulatory micro-ribonucleic acid (miRNA) profiles in patients on chronic haemodialysis therapy. METHODS: We will perform a quasi-experimental study in 3 dialysis centres. Patients will be recruited via their nephrologists and will be allocated to an experimental and a control group based on the location of the patients' dialysis centre. Patients allocated to the experimental group will undergo a 12-week IRT, while the control group will remain physically inactive during dialysis. The primary outcome is the change in the maximal force produced during an isometric contraction of lower extremity muscles. Secondary outcomes regard quality of life, anxiety and depression, clinical outcomes and circulatory miRNA profiles. Patients' level of health literacy defined as the ability to get and understand health information will be also measured in the study as a potential modifier of effects. DISCUSSION: This quasi-experimental study can add in an important way to our understanding of the effects of resistance training on dialysis patients' muscle strength, quality of life and disease-specific outcomes.
Keywords: Renal Dialysis; chronické selhání ledvin; dialýza ledvin; úzkost; výsledek terapie; Resistance Training; svalová síla; Multicenter Studies as Topic; kvalita života; lidé; Treatment Outcome; klinická studie jako téma; Anxiety; Clinical Studies as Topic; Kidney Failure, Chronic; Muscle Strength; isometrická kontrakce; multicentrické studie jako téma; Isometric Contraction; mikro RNA; MicroRNAs; deprese; Depression; Quality of Life; odporový trénink; Humans